Modulation of Endothelin-1 and Placental Microvascular Diameter by Extra Virgin Olive Oil in Preeclampsia Rat Model - Dian Lovita, Agnestia Naning; Silvani, Yulia; Maharani, Afniari; Riawan, Wibi (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Preeclampsia is linked to abnormal placental vasoconstriction and elevated endothelin-1 (ET-1). Polyphenols in Extra Virgin Olive Oil (EVOO) has antioxidant and vasoprotective properties, but its impact on ET-1 and placental microvasculature in preeclampsia is unclear. Objective: Investigate whether EVOO can attenuate hypertension and improve placental vascular health in preeclampsia. Method: 20 pregnant rats randomly assigned to five groups: normal (K−), preeclampsia model (K+), and three EVOO-treated groups (D1, D2, D3) receiving 0.5, 1, and 2 mL/day, respectively. Preeclampsia was induced with L-NAME, blood pressure was monitored on gestational days 12, 15, and 19. Placental ET-1 expression and microvessel diameter were assessed on day 19 using immunohistochemistry. Result and Discussion: EVOO treatment normalized blood pressure by gestational day 19. ET-1 expression increased with EVOO dose suggesting a role in vascular remodelling. Microvessel diameter improved in D1 and D2 but slightly decreased in D3. Conclusions: EVOO mitigates hypertension and enhances placental microvasculature in preeclampsia, with optimal effects at moderate doses.